Natural variations of TFIIAγ gene and LOB1 promoter contribute to citrus canker disease resistance in Atalantia buxifolia - Tang, Xiaomei; Wang, Xia; Huang, Yue; Ma, Ling; Jiang, Xiaolin; Rao, Muhammad Junaid; Xu, Yuantao; Yin, Ping; Yuan, Meng; Deng, Xiuxin; Xu, Qiang (PLoS genetics, 2021)
Citrus canker caused by Xanthomonas citri subsp. citri ( Xcc ) is one of the most devastating diseases in citrus industry worldwide. Most citrus cultivars such as sweet orange are susceptible to canker disease. Here, we utilized wild citrus to identify canker-resistant germplasms, and found that Atalantia buxifolia , a primitive (distant-wild) citrus, exhibited remarkable resistance to canker disease. Although the susceptibility gene LATERAL ORGAN BOUNDARIES 1 ( LOB1 ) could also be induced in Atalantia after canker infection, the induction extent was far lower than that in sweet orange. In addition, three of amino acids encoded by transcription factor TFIIAγ in Atalantia (AbTFIIAγ) exhibited difference from those in sweet orange (CsTFIIAγ) which could stabilize the interaction between effector PthA4 and effector binding element (EBE) of LOB1 promoter. The mutation of AbTFIIAγ did not change its interaction with transcription factor binding motifs (TFBs). However, the AbTFIIAγ could hardly support the LOB1 expression induced by the PthA4. In addition, the activity of AbLOB1 promoter was significantly lower than that of CsLOB1 under the induction by PthA4. Our results demonstrate that natural variations of AbTFIIAγ and effector binding element (EBE) in the AbLOB1 promoter are crucial for the canker disease resistance of Atalantia. The natural mutations of AbTFIIAγ gene and AbLOB1 promoter in Atalantia provide candidate targets for improving the resistance to citrus canker disease.